Penerapan Media Bioflok Dalam Budidaya Ikan Lele Dumbo Dan Ikan Gurame Di Desa Kejuden Kecamatan Depok Kabupaten Cirebon - Nurlaeli, Nurlaeli; Ekawati, Nurul; Novianti, Teni (Alpatih Harapan Semesta, 2024)
Fish farming is an effort to utilize the resources around to achieve a common goal in a group, This activity is carried out in order to produce fish in a controlled and profit-oriented container or media. It is hoped that the products produced will be multiplied and abundant. After field observations in Kejuden Village, there is some information that the problems faced by fish farmers due to limited resources such as land and water are the main obstacles in dumbo catfish cultivation and carp farming, especially in areas with high population density such as Kejuden Village. One of them is the use of biofloc media. In this study, the researcher used a case study research method. is a research procedure that produces descriptive data obtained from informants in the field, The data collection techniques used are interviews, and observations. Based on the results of research in the field, biofloc fish cultivation techniques have been applied such as feeding, probiotic administration and fish pond maintenance, but there are several techniques that are not applied such as water quality measurement, temperature, fish growth monitoring and weight monitoring per fish. Based on the results of the study, the researcher concluded that there are several stages in the cultivation process, namely the preparation stage, both land preparation, broodstock, spawning, and other facilities that support the catfish cultivation process. The land preparation in question is the preparation of a pond for catfish cultivation. There are various types of mini kola such as earthen ponds, tarpaulin ponds, and cast ponds, or even by using other media that have currently been developed so that the process of cultivating catfish using biofloc requires a lot of great preparation.